HydroCoil for Endovascular Aneurysm Occlusion (HEAL) Study: Periprocedural Results - Cloft, H.J. (AJNR Am J Neuroradiol, 2006)
BACKGROUND AND PURPOSE: The HydroCoil Embolic System (HES) was developed to improve the efficacy of endovascular treatment of cerebral aneurysms. The purpose of this study is to study the periprocedural results in patients with cerebral aneurysms treated with HES. METHODS: We report the initial periprocedural results in 191 cerebral aneurysms treated with HES in the HydroCoil for Endovascular Aneurysm Occlusion, or HEAL, study. Initial aneurysm occlusion and periprocedural complication rates were evaluated and compared with historical control data regarding aneurysms treated with platinum coils. RESULTS: An initial occlusion result of “complete” or “near-complete” was achieved in 91.8% of aneurysms. Periprocedural thromboembolic events occurred in 8.1% of aneurysms treated with neurologic deficits related to thromboemboli occurring in 2.1% of aneurysms treated. Intraprocedural aneurysm perforations occurred in 2.8% of previously ruptured aneurysms, and in 0% of previously unruptured aneurysms. CLUSION: The initial occlusion success and complication rate when HES is used to treat cerebral aneurysms is not significantly different from platinum coils. Follow-up angiography is currently being collected and will be evaluated to determine if use of the HES reduces the rate of aneurysm recurrence.